Strengthening Students’ Mathematics Reasoning Ability Through Brain Based Learning Model Meets Active Learning Approach - Wahyuti; Deni Hardianto (South Sulawesi Education Development (SSED), 2025)
This study was motivated by the difficulty of students in Klaten District Gugus IV to understand division material. Through preliminary studies and small-scale research, a learning model that can help students in reasoning to improve thinking skills was found. The model is a brain-based learning model integrated with an active learning approach. Due to the collaboration and implementation of this model and approach, students experienced an increase in the results of mathematical reasoning ability by 28.11. This research was conducted in grade 3 of SDN 1 Mundu with 30 students in each experimental and control class group. Through the independent test, a significance of 0.000 was obtained from the implementation of the brain-based learning model with an active learning approach which states that there is a significant effect on changes in students' mathematical reasoning ability.